(untitled) (Journal of Rural Sociology, Microfinance, and Poverty Studies, 2024)
The adage “Ang kahirapan ay hindi hadlang sa pag-aaral” translates to “Poverty is not a hindrance to education,” highlighting the determination and resilience of students facing economic adversity in their pursuit of academic success. Despite the challenges posed by low socioeconomic status, education is viewed as a vital avenue for empowerment and socioeconomic advancement, with students often balancing work and study to overcome financial constraints. This study seeks to address a gap in the literature by delving into the lived experiences of students confronting poverty. Employing a phenomenological research design, the study explores how students navigate poverty while pursuing their education. Purposive sampling was utilized, selecting five college students from low socioeconomic backgrounds to offer rich insights into overcoming financial barriers. Data was collected through semi-structured, in-depth interviews, transcribed verbatim, and analyzed using narrative analysis to identify key themes and patterns. The study reveals significant themes such as poverty’s financial and emotional impacts, strategies employed to overcome economic hardships, and the pivotal roles of perseverance and motivation in attaining academic success. Participants emphasized the importance of dedication and effort over financial resources. These findings underscore the necessity of supporting underprivileged students through counseling services and mentorship programs. Additionally, the study suggests further research to explore the long-term outcomes and effectiveness of support interventions.